IRSp53 senses negative membrane curvature and phase separates along membrane tubules - Prévost, Coline; Zhao, Hongxia; Manzi, John; Lemichez, Emmanuel; Lappalainen, Pekka; Callan-Jones, Andrew; Bassereau, Patricia (Nature communications, 2015)
BAR domain proteins contribute to membrane deformation in diverse cellular processes. The inverted-BAR (I-BAR) protein IRSp53, for instance, is found on the inner leaflet of the tubular membrane of filopodia; however its role in the formation of these structures is incompletely understood. Here we develop an original assay in which proteins are encapsulated in giant unilamellar vesicles connected to membrane nanotubes. Our results demonstrate that I-BAR dimers sense negative membrane curvature. Experiment and theory reveal that the I-BAR displays a non-monotonic sorting with curvature, and expands the tube at high imposed tension while constricting it at low tension. Strikingly, at low protein density and tension, protein-rich domains appear along the tube. This peculiar behaviour is due to the shallow intrinsic curvature of I-BAR dimers. It allows constriction of weakly curved membranes coupled to local protein enrichment at biologically relevant conditions. This might explain how IRSp53 contributes in vivo to the initiation of filopodia. The inverted-BAR domain protein IRSp53 associates with the inner leaflet of tubular membranes such as filopodia. Here, Prévost et al . demonstrate that the I-BAR domain of IRSp53 senses negative membrane curvature, and undergoes phase separation which may aid its clustering upon filopodia generation.